Factors that affecting the acceptance of internet banking at Majlis Perbandaran Johor Bahru Tengah / Zuleyana Kasiran and Nurul Najwafildzah Hamim - Kasiran, Zuleyana; Hamim, Nurul Najwafildzah (2014)
Internet banking is becoming new focuses as the number of internet users is increasing globally and its benefits. (Yeoh S.F & Benjamin C.Y.F, 2011). The implementation of Internet Banking becomes a necessity for every bank to ensure that they are able to compete in the global market. (Hassan N.A et al, 2012). This research investigates the factors that affecting the acceptance of internet banking at MPJBT. It is an essential part of MPJBT to increase the level of internet banking usage among customer at MPJBT. Survey based on questionnaire design was carried out. The results have supported the hypothesis. 100 questionnaires have been distributed among the public at MPJBT. The data obtained were analyzed in SPSS 20.0 which involves reliability test, frequencies, Pearson Correlation Coefficient and regression analysis. The study also attempt to identify the factor that most affecting the acceptance of internet banking among those investigated which are trust, attitude and ease of use. Based on the findings, trust is found to have a significant relationship towards the acceptance of internet banking but both attitude and attraction were found to have no significant relationship toward the acceptance of internet banking. Moreover, trust is found to be the most factor that affecting the acceptance of internet banking. The findings achieved in this study will be of interest for MPJBT in order to increase their customer who using internet banking.